Ethiopian animal husbandry: A handbook - Wilson, R.T. (1991)
Discusses the production systems of small ruminants in tropical Africa with particular reference to types of sheep and goats. Topical discussions on synonyms, sub-types, race characteristics, distribution, origin, ecological zones, their products, productivity and reproduction included.